THE NEUTRALITY OF TAXATION OF INVESTMENT PROJECTS IN SERBIA - Luković, Stevan; Vržina, Stefan; Grbić, Milka; Pjanić, Miloš (Economic Annals, 2021)
The paper analyses the neutrality of taxation of investment projects on the example of Serbia. The aim of the research is to confirm/reject the existence of uniformity of the tax burden on investment projects that differ regarding the asset type, industry and the source of finance. The uniformity of tax burden, that is, the absence of discrimination and distortive effects of taxation, may be considered a confirmation of the tax neutrality. To investigate neutrality of taxation the analysis employed King-Fullerton framework of calculating effective marginal tax rates. The research results show that the tax treatment of investment projects in Serbia is nondiscriminatory. Marginal effective tax rates for different types of investment projects do not vary widely; that is, there are no investment projects that have a markedly favourable (unfavourable) tax treatment compared to the other types of investment projects.